2018
DOI: 10.1103/physrevd.98.043532
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the cosmic shear data flood: Optimal data extraction and simulation requirements for stage IV dark energy experiments

Abstract: Upcoming photometric lensing surveys will considerably tighten constraints on the neutrino mass and the dark energy equation of state. Nevertheless it remains an open question of how to optimally extract the information and how well the matter power spectrum must be known to obtain unbiased cosmological parameter estimates. By performing a principal component analysis (PCA), we quantify the sensitivity of 3D cosmic shear and tomography with different binning strategies to different regions of the lensing kerne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…This is complementary to the conclusions of [13] who find that for a sufficiently large number of bins both an equal-number and equal-spaced configuration captures all the 3D information from the shear field, but that as the number of bins increased the equal-number case converges more slowly than the equal-spaced case. The reason why equally-spaced bins are optimal is two-fold: the bins are orthogonal, and the equal-spacing provides better redshift coverage for dark energy measurements.…”
Section: Best Fitsupporting
confidence: 72%
See 2 more Smart Citations
“…This is complementary to the conclusions of [13] who find that for a sufficiently large number of bins both an equal-number and equal-spaced configuration captures all the 3D information from the shear field, but that as the number of bins increased the equal-number case converges more slowly than the equal-spaced case. The reason why equally-spaced bins are optimal is two-fold: the bins are orthogonal, and the equal-spacing provides better redshift coverage for dark energy measurements.…”
Section: Best Fitsupporting
confidence: 72%
“…The most widely used cosmic shear power spectrum formulation uses the Limber [10], flat-Universe [11] and equal-time [12] approximations, and creates bins in redshift known as 'tomographic' bins. This approach was generalised in [13] to a generalised spherical-transform that is defined as:…”
Section: Cosmic Shear Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile we refer to the information contained in these amplitudes and functions as the nonparametric information. This study directly builds off [20] where we found the precise scales and redshifts where cosmic shear is sensitive to the power spectrum and comoving distance.…”
Section: Introductionmentioning
confidence: 72%
“…We choose to use the shear two-point statistic. Even though this only accesses the Gaussian information of the shear field, a large body of work exists to provide rigorous requirements on systematics to ensure unbiased results [19][20][21].…”
Section: Introductionmentioning
confidence: 99%